Inconsistent Responses of Transpiration of Different Canopy Layers to Simulated Canopy and Understory N Depositions in a Low‐Subtropical Evergreen Broadleaf Forest. Issue 5 (22nd May 2020) - Li, Yanqiong; Zhao, Ping; Zhang, Zhenzhen; Zhu, Liwei; Ouyang, Lei; Ni, Guangyan
Abstract: Quantifying transpiration and its response to meteorological factors at a stand scale and different canopy layers of forest is important for understanding the hydrological impact of nitrogen (N) deposition on local water balance. For this purpose, sap flows were measured in three upper ( Schima superba, Castanea henryi, and Machilus chinensis ) and three lower ( Symplocos ramosissima, Ilex ficoidea, and Schefflera octophylla ) canopy species based on a manipulative experimental platform with canopy (CN) and understory (UN) N additions in a low‐subtropical evergreen broadleaf forest. Each application included concentrations of 0, 25, and 50 kg·ha −1 ·a −1 N. Results showed that N addition obviously influenced the sap flux density and such influence varied among different species and between canopy layers. Upper canopy species contributed the most transpiration for the whole forest, and CN25 greatly affected the transpiration in both upper and lower canopy layers. Daily water use ( Q d ) increased logarithmically with daytime average photosynthetically active radiation and daily average vapor pressure deficit. An appropriate canopy N addition (CN25) promoted the Q d and its sensitivity to micrometeorological factors, whereas UN had a minimal effect. These results suggest a substantial difference in response of transpiration to the N addition ways. CN had more effective influence on the canopy transpiration. Thus, UN could not fully reflect the effects of increased N deposition on the canopy‐associated transpiration, and the response of forest transpiration to N deposition needs to be analyzed beyond species and upscaled to the canopy level in favor of meaningful assessments of N deposition. Key Points: Transpiration response to N deposition needs to be analyzed beyond species and upscaled to forest canopy to achieve meaningful assessments Subtropical forests adapt to increased N deposition through the sensitivity adjustment of transpiration to meteorological factors An appropriate canopy N addition promoted the forest transpiration and its sensitivity to meteorological factors